Phylogeography and genetic diversity of Pieris rapae across continents - Md. Ahashan Habib Siam; D. Dey; J. K. Owaresat; Yousha Shamim Khan; Efrin Anowar; J. F. Maya; AMAM Zonaed Siddiki (PLoS ONE, 2026)
The small cabbage white butterfly ( Pieris rapae ) is a globally distributed agricultural pest that has successfully colonized most continents through natural and human-mediated dispersal. This study investigates the global genetic diversity and phylogeographic structure of Pieris rapae using mitochondrial cytochrome c oxidase subunit I (COI) sequences. A total of 1,133 sequences from five continents (Africa, Asia, Europe, North America, and Oceania) were analyzed to assess haplotype diversity, nucleotide diversity, population structure, and evolutionary relationships. Across the dataset, 117 haplotypes were identified, with overall high haplotype diversity (Hd = 0.8635) and moderate nucleotide diversity (π = 0.00610). Europe exhibited the highest genetic diversity, while North America showed low haplotype diversity but comparatively high nucleotide divergence, suggesting multiple introduction events. Minimum spanning network analysis revealed a star-like pattern with several widely shared central haplotypes, indicating recent expansion and extensive dispersal. Phylogenetic analysis identified two major mitochondrial clades, with North American haplotypes distributed across both clades. AMOVA results showed that most genetic variation occurred within populations (71.62%), although significant differentiation existed among continents (FST = 0.28385, p < 0.05). Pairwise FST and gene flow estimates indicated restricted intercontinental gene exchange, while the Mantel test showed no significant isolation by distance. Overall, the results suggest a complex invasion history shaped by historical introductions, demographic expansion, and human-mediated dispersal.